Foot and ankle angioleiomyoma: a systematic review - Michaël J. Matos; Sérgio Soares; Joseph M. Schwab; Moritz Tannast; Angela Seidel (BMC Musculoskeletal Disorders)
Abstract Background Angioleiomyoma is a benign tumor arising from smooth muscle that is commonly found in the foot and ankle. This systematic review aims to synthesize the limited data from numerous case reports and case series, which often involve small sample sizes, to provide orthopaedic surgeons with a comprehensive overview of the diagnosis and management of foot and ankle angioleiomyoma. Methods This systematic review, performed following the PRISMA guidelines, brings updated information for the diagnosis and management of foot and ankle angioleiomyoma. 62 relevant studies were included. We analysed patient demographics, clinical characteristics, diagnostic workup, treatment, and clinical outcomes. Results Angioleiomyoma is more prevalent in middle-aged women, and pain is the most common symptom. Its diagnosis is often delayed due to its rarity and nonspecific presentation. Plain radiographs, MRI, and ultrasound of the foot and ankle are the most common preoperative imaging exams. Surgical excision is the treatment of choice with a low rate of both recurrence and malignant transformation. Conclusions This review emphasizes the importance of considering angioleiomyoma in the differential diagnosis of foot and ankle tumors and highlights the need for a comprehensive workup to improve diagnostic accuracy and ensure appropriate management.